Climate change: time to Do Something Different - Page, Nadine; Page, Mike (Frontiers in Psychology, 2014)
There is now very little, if any, doubt that the global climate is changing and that this is in some way related to human behaviour through unsustainable preferences in lifestyle and organisational practices. Despite the near conclusive evidence of the positive relationship between greenhouse gas emissions and global warming, a small proportion of people remain unconvinced. More importantly, even among the much larger number of people who accept a link between human behaviour and climate change, many are inactive, or insufficiently active, in attempting to remedy the situation. We suggest this is partly because people are unaware both of how their day-to-day behaviours connect with energy consumption and carbon emissions, and of the behavioural alternatives that are available to them. This, we believe, is a key reason why individual lifestyles and organisational practices continue in an unsustainable way. We also suggest that the psychologists and behavioural researchers who seek to develop a better understanding of people’s relationship with, and reaction to, environmental issues, might also be on track to suffer a similar blindness. They risk becoming fixed on investigating a limited range of established variables, perhaps to the detriment of alternative approaches that are more practically oriented though, so far, less well explored empirically. In this article, we present the FIT framework as an alternative perspective on the variables that might underpin pro-environmental activity and behaviour change. After briefly reviewing the related literature, we outline that framework. Then we present some early empirical data to show its relationship to a range of pro-environmental indices. We follow with a discussion of the framework’s relevance in relation to pro-environmental behaviour change and make proposals for future research.